Biomedical cellular product for wound healing. Issue 1 (2015) - Lykov, Alexander P; Bondarenko, Natalia A; Poveshchenko, Olga V; Miller, Tatjana V; Poveshchenko, Alexander F; Surovtseva, Maria A; Bgatova, Natalia P; ,; Konenkov, Vladimir I
No abstract available